Malaria Vectors Insecticides Resistance in Different Agroecosystems in Western Kenya - Wanjala, Christine Ludwin; Kweka, Eliningaya J. (Frontiers in Public Health, 2018)
Background: Malaria vector control efforts have taken malaria related cases down to appreciable number per annum after large scale of intervention tools. Insecticides based tools remain the major control option for malaria vectors in Kenya and therefore the potential of such programs to be compromised by the reported insecticide resistance is of major concern. The objective of this study was to evaluate the status of insecticide resistance in malaria vectors in different agro ecosystems from western Kenya. Methods: The study was carried out in the lowlands and highlands of western Kenya namely; Ahero, Kisian, Chulaimbo, Emutete, Emakakha, Iguhu and Kabula. World Health Organization tube bioassays was conducted using standard diagnostic dosages of Lambdacyhalothrin, Deltamethrin, Permethrin, DDT, Bendiocarb and Malathion tested on Anopheles mosquitoes collected from seven sites; Ahero, Kisian, Chulaimbo, Emutete, Emakakha, Iguhu and Kabula. Biochemical assays, where the enzymatic activity of three enzymes (monooxygenases, esterases and Glutathione S-transferases) were performed on susceptible and resistant mosquito populations. Wild mosquito populations were identified to species level using Polymerase Chain Reaction. The species of the wild mosquito populations were identified to species level using Polymerase Chain Reaction. Real-Time polymerase chain reaction was performed on the susceptible and resistant mosquitoes after the WHO tube bioassays to determine the presence of kdr allele. Results: WHO susceptibility tests indicated that An. gambiae showed resistance to Pyrethroids and DDT in all the study sites, to Bendiocarb in Iguhu and Kabula and susceptible to Malathion (100% mortality) in all the study sites. There was an elevation of monooxygenases and esterases enzymatic activities in resistant An. gambiae mosquito populations exposed to Lambdacyhalothrin, Permethrin, Deltamethrin and DDT but no elevation in glutathione s- transferases. A high frequency of L1014S allele was detected in An. gambiae s.s. population but there was no kdr allele found in An. arabiensis mosquitoes. Conclusion: Anopheles gambiae mosquitoes from western Kenya have developed phenotypic resistance to pyrethroids and DDT. Therefore there is a need for further research covering different climatic zones with different agro-economic activities for detailed report on current status of insecticide resistance in malaria vectors.